Paul and his theology - Porter, Stanley E., 1956- (Pauline studies, 2006)
Does Paul have a theology? If so, what is it, or rather, what is it on various topics that he and the early Church confronted? This volume moves beyond the traditional discussion of whether Paul had a center to his theology to raise questions regarding his perspective on a number of important theological issues. These issues include his gentile mission, the concepts of faith, grace, and the law, reconciliation, the temple, eschatology, miracles, gender, and Paul's trinitarian tendencies. This collection of essays addresses topics of current interest in the study of Paul's theology, not to arrive at the center of his thought, but to understand what factors helped to center his thinking on a variety of important theological concerns.